"Loud, proud, and love a crowd:" African American girls and school discipline practices. Issue 1 (1st January 2020) - Walker, Brenda L. Townsend
Abstract: Historically, middle grade schools doled out the harshest and most exclusionary discipline to adolescent African American males. African American males were routed along school to prison pathways at rates higher than African American females and their peers from other racial backgrounds. National conversations about exclusionary discipline practices and the school-to-prison pipeline have focused primarily on African American males. More recently, however, African American girls experience exclusionary discipline practices and school-to-prison pathways at rates that, in some cases, exceed African American males. Consequently, national conversations can no longer be single-gendered. African American girls must also be central to dialogues on school discipline and the school-to-prison pipeline. This paper shines klieg lights on middle grade African American girls' subjection to exclusionary school discipline, school-to-prison pipelines, and negative and stereotypical perceptions. Lastly, this author draws from the literature and her experiences working with middle grade African American girls with multiple school suspensions. She concludes the discussion with culturally responsive recommendations for equitable school discipline practices.